KUALITAS INTERNAL AUDITOR DAN BIAYA AUDIT DALAM PENENTUAN KUALITAS AUDIT - Dharma Dhatu (Jurnal Akuntansi Kontemporer, 2020)
Objective of this studies is to explain effect of auditor internal quality and audit fee on audit quality. Data collected by questionnaires to auditors who working in Public Accountant Firm. The population of this study were public accountants working at Jakarta and Tangerang. Sample selection using convenience method and using primary data. Respondent of this study were auditors that have at least one year work experience and work as senior auditors and had carried out all of the audit process. 201 questionnaires distributed, but only 179 questionnaires returned and 101 questionnaires can be used for analyzed in this research using multiple linear regressions. The results of this study were (1) professionalism had significant effect on auditor audit quality, (2) audit risk had significant effect on audit quality, (3) time budget pressure had no effect on audit quality and (4) audit fee had significant effect on audit quality.